2017
DOI: 10.1103/physrevd.96.074005
|View full text |Cite
|
Sign up to set email alerts
|

Cumulant expansion in gluon saturation and five- and six-gluon azimuthal correlations

Abstract: Correlations between the momenta of the final state hadrons measured in proton or nucleus collisions contain information that sheds light on the initial conditions and evolutionary dynamics of the collision system. These correlation measurements have revealed the long-range rapidity correlations in p-p and p-Pb systems, and they have also made it possible to extract the elliptic flow coefficient from hadron correlation measurements. In this work, we calculate five-and six-gluon correlation functions in the fra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…[ [29][30][31], we suggested that investigating the three-hadron correlations could rule out one of the two mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…[ [29][30][31], we suggested that investigating the three-hadron correlations could rule out one of the two mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, multiparticle dynamics in the regime of soft momenta p T < Q s,T is sensitive to the dynamics of several color domains of size 1/Q s,T ; in contrast, for p T ≥ Q s,T , the physics is sensitive to dynamics within a given domain. For large p T > Q s,T , the quasiparticle nature of color fields is relevant and the QCD dynamics can be represented in terms of Feynman diagrams, the so-called Glasma graphs [36,37,38,39,40,41,42,43,44]. In the kinematic regime of p T Q s,T , they provide a good description of the ridge.…”
Section: Introductionmentioning
confidence: 99%